1986
DOI: 10.1530/acta.0.1130450
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms of 6-sulphatoxy melatonin, cortisol and electrolyte excretion at the summer and winter solstices in normal men and women

Abstract: Abstract. Urinary excretion of 6-suphatoxy melatonin, cortisol, potassium and sodium was monitored at four hourly intervals for 24 h in 30 normal subjects at the summer and winter solstices. The 24 h profiles were fitted to sine curves and mean 24-h excretion, time of maximum excretion and amplitude of the curves compared. The excretion of 6-sulphatoxy melatonin was remarkably stable at the two times of the year (24-h excretion 108 ± 6.3 nmol in summer and 105 ± 6.3 nmol in winter, mean ± sem). The time of max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…During the winter, melatonin circadian rhythm also displays a phase shift towards the morning hours [63], [64], [66], [67], [86][88], with shorter duration of melatonin excretion [79] which could attenuate seasonal differences in melatonin levels if samples are collected in the morning, as they were in our study.…”
Section: Discussionmentioning
confidence: 60%
“…During the winter, melatonin circadian rhythm also displays a phase shift towards the morning hours [63], [64], [66], [67], [86][88], with shorter duration of melatonin excretion [79] which could attenuate seasonal differences in melatonin levels if samples are collected in the morning, as they were in our study.…”
Section: Discussionmentioning
confidence: 60%
“…In this study, despite some differences in light exposure between seasons, the timing of the DLMO at the end of the working week did not differ between summer and winter. Other studies have reported a delayed melatonin phase in winter compared to summer, but again these were studies of people with presumably more flexible schedules than full-time office workers (Honma et al, 1992; Illnerova et al, 1985; Kennaway and Royles, 1986). The timing of the DLMO significantly correlated with the first exposure to 10 lux, which occurred shortly after waking indoors.…”
Section: Discussion/conclusionmentioning
confidence: 98%
“…This hypothesis of diminishing sunlight exposure is supported by studies of blood melatonin, the nighttime hormone whose secretion by the pineal gland should be inversely related to day length. Several studies conducted around the 1980s failed to find an annual rhythm in the blood levels of melatonin among normal, urbanized American or European subjects (Illnerová et al,1985; Kennaway and Royles,1986; Wehr et al,1995). This was explained in the latter study in terms of artificial lighting suppressing the normal response to the natural photoperiod.…”
Section: Resultsmentioning
confidence: 99%